Improving education for incarcerated children and young people: policy recommendations from three transnational projects in Europe - Adeela ahmed Shafi (Quality Education for All)
Purpose – The purpose of this policy piece is to present headline evidence from the equivalent of a decade of research across three projects focused on improving the educational experiences of incarcerated or justice-involved children and young people across 14 countries. The projects demonstrated a positive impact when using the specially designed innovative methods even with disengaged justice-involved children and young people. Each project had a different focus based on the needs of the children and young people, including (re)engaging them with education and learning opportunities re-engaging young offenders with education and learning (RENYO), developing identified social and emotional competencies through sport active games 4 change (AG4C) and developing skills for when transitioning into communities (S4L). Design/methodology/approach – Each of the three projects designed bespoke interventions and materials based on the focus of the project. Combined, these were piloted across a total of 14 countries with 548 children and young people, 225 educators and 21 youth justice settings (custodial and non-custodial). Qualitative and quantitative data were gathered from educators, children and young people to better understand the effectiveness and limitations of the pedagogical approaches, the materials and experiences of the users. Findings – The findings from across the three projects demonstrated that when custodial settings or youth justice settings have greater access to specifically designed tools and resources, with appropriate training to use them, it is possible to re-engage even the most disengaged children and young people with education and learning (RENYO). It was also possible to show a statistically significant increase in social and emotional competencies (social awareness, responsible decision-making, self-awareness, self-management, relationship skills) in participating country settings (AG4C) and to engage children and young people with a Skills4Life Curriculum in preparation for moving back into the community. Research limitations/implications – Custodial and other youth justice settings vary widely in different jurisdictions with varying levels of resource. Whilst all programmes had success in implementation, this was to different degrees and extents in each of the country contexts. Much of this success will depend on the skills of educators and the willingness of the leadership. Practical implications – The programmes and interventions in this policy piece can be used in a range of contexts and settings as shown by the wide range of sites they were piloted in. From a practical perspective, these programmes and interventions have been designed to fit into existing structures and timetables with custodial and youth justice settings, making them easily integrated into business as usual. Originality/value – Planned and strategically delivered interventions by expert educators in a holistic way means there is real opportunity to better support justice involved children and young people to successful transitioning back into communities, thereby potentially reducing reoffending. This is done by (re)engaging them with education and learning on entry, using the authentic inquiry methodology, developing social and emotional competencies through the active games and sport programme, followed by a tailored Skils4Life Curriculum preparing them for transition back into communities.